Personal Branding: Mengangkat Potensi Diri dan Usaha UMKM - Qahfi, Andi Muhammad Ashabul; Hermansyah, Fakhrul Indra (Jaanur ElBarik Indonesia, 2025)
This community service activity aims to improve the skills of MSMEs, village youth, final-year students, and local communities in building effective personal branding as a strategy to expand the market and increase competitiveness. The implementation method included socialization and interactive training on creating a brand visual identity (logo, typography, color). Evaluation results showed that the majority of participants successfully created a consistent, representative, and business-characterized brand identity, and were able to operate social media accounts professionally. There was an increase in branding skills, content creativity, and participants' confidence in promoting products or services. This program not only provided technical skills but also encouraged the formation of a sustainable positive branding culture within the Sanjai Village community. The success of this activity is expected to serve as a foundation for developing a broader digital marketing strategy in the future